STUDY ON THE INFLUENCE OF NATURAL Biostimulators on the Growth of Plants - Brodeckaya V.V. (Biomedicinskaâ Inženeriâ i Èlektronika, 2017)
The paper presents the results of observations on plant growth, which was influenced by natural biostimulants. In the course of research, phenological observations and morphological observations were performed. As a result of the work, it was noted that biostimulants allow to reduce the number of days after plant development, increase the number of leaves and lateral shoots, well formed assimilation apparatus